The design and testing of an exhaust air energy recovery wind turbine generator / Ahmad Fazlizan Abdullah - Ahmad Fazlizan, Abdullah (2012)
An innovative system to recover part of the energy from man-made wind resources (exhaust air systems) is introduced. A vertical axis wind turbine (VAWT) in cross-wind orientation, with an enclosure is mounted above a cooling tower’s exhaust fan to harness the wind energy for producing electricity. The enclosure is designed with several guide-vanes to create a venturi effect (to increase the wind speed) and guide the wind to the optimum angle-of-attack of the turbine blades. Another feature of the enclosure is the diffuser-plates that are mounted at a specific angle to accelerate the airflow. Moreover, safety concerns due to blade failure or maintenance activities are tackled by the design of the enclosure. The performance of the VAWT and its effects on the cooling tower were investigated. Laboratory test conducted on a scaled model (with a 5-bladed H-rotor with 0.3 meter rotor diameter) shows no measureable difference on the air intake speed (1.6~1.8 m/s) and current consumption of the power-driven fan (0.39 ampere) when the turbine was spinning on top of the scaled model of the cooling tower. Field test on the actual induced-draft cross flow cooling tower with 2 meters outlet diameter and powered by a 7.5 kW motor was performed using a 3-bladed Darrieus wind turbine with 1.24 meter rotor diameter. There were no significant differences on the outlet air speed of the cooling tower, i.e. the outlet speed of the cooling tower without and with wind turbine was 10.63 m/s and 10.67 m/s respectively (the rotational speed of the turbine was 881 rpm). No measureable difference was observed on the power consumption which was recorded between 7.0 to 7.1 kW for both cases. This system is retrofit-able to the existing cooling towers and has very high market potential due to abundant cooling towers and other unnatural exhaust air resources globally. In addition, the energy output is predictable and consistent, allowing simpler design of the downstream system.